2015
DOI: 10.3389/fimmu.2015.00272
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Systemic Sclerosis

Abstract: Systemic scleroderma (SSc) is one of the most complex systemic autoimmune diseases. It targets the vasculature, connective tissue-producing cells (namely fibroblasts/myofibroblasts), and components of the innate and adaptive immune systems. Clinical and pathologic manifestations of SSc are the result of: (1) innate/adaptive immune system abnormalities leading to production of autoantibodies and cell-mediated autoimmunity, (2) microvascular endothelial cell/small vessel fibroproliferative vasculopathy, and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
338
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(348 citation statements)
references
References 455 publications
(592 reference statements)
4
338
0
6
Order By: Relevance
“…ystemic sclerosis (SSc) is a connective tissue disorder characterized by fibrosis of the skin and inner organs, vascular alterations, and dysimmunity including the presence of autoantibodies to nuclear proteins (1). The cause of this disease remains unknown, and its understanding is further complicated by its inherent heterogenous clinical manifestations (2).…”
mentioning
confidence: 99%
“…ystemic sclerosis (SSc) is a connective tissue disorder characterized by fibrosis of the skin and inner organs, vascular alterations, and dysimmunity including the presence of autoantibodies to nuclear proteins (1). The cause of this disease remains unknown, and its understanding is further complicated by its inherent heterogenous clinical manifestations (2).…”
mentioning
confidence: 99%
“…Systemic sclerosis (SSc) is one of the most complex systemic autoimmune diseases [1] characterized by cutaneous and visceral fibrosis, immune dysregulation and vasculopathy [2]. The interplay of these three processes determines the clinical and pathologic manifestations of the disease [1].…”
Section: Editorialmentioning
confidence: 99%
“…The interplay of these three processes determines the clinical and pathologic manifestations of the disease [1]. The core signs and symptoms of SSc are Raynaud's phenomenon, skin thickening and serum autoantibody production, but patients have different patterns of internal organ involvement with variable presentations and outcomes [3].…”
Section: Editorialmentioning
confidence: 99%
“…Vitamin D has been extensively studied as an anti-fibrotic agent in non-neoplastic chronic diseases and a number of studies have shown that the myofibroblast is a main target cell of 1,25(OH) 2 D 3 inhibitory action (reviewed in 45,46). A main and recurring finding has been that 1,25(OH) 2 D 3 interferes with the pervasive pro-fibrotic action of TGF-β: this inhibitory effect is predictable since calcitriol, on its own, represses collagen synthesis in a variety of cells (47,48).…”
Section: Vitamin D and Fibrosismentioning
confidence: 99%